Teachers' strategies in teaching quran memorization at luqmanul hakim batumarta ii islamic boarding school - Rina Sari; Heri Sepriyadi; Dadang Nurdin (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the strategies employed by tahfidz teachers in Qur’anic memorization learning and the factors influencing their success. Using a qualitative approach with a case study method, data were collected through observation, in-depth interviews, and documentation at a formal educational institution offering a tahfidz program. The findings indicate that tahfidz teachers implement various creative strategies, including talaqqi, tikrar, verse mapping, and the use of digital media to enhance student engagement. Supporting factors include teachers’ spiritual commitment, well-structured tahfidz programs, and parental involvement. Conversely, limited time allocation, low student motivation, and inadequate pedagogical training are identified as major obstacles. The study concludes that effective tahfidz instruction must be adaptive, contextual, and supported by strong collaboration among teachers, institutions, and families. The findings imply the need for professional development for tahfidz teachers and the enhancement of curriculum design aligned with students’ psychopedagogical needs.